(untitled) (Journal of Advanced Research in Social Sciences, 2021)
Strategic partnership represents one of the essential tools of inter-state engagement in International Relations, primarily from the post-Cold War period. Contrary to the erstwhile partnership agreements, the nature of alignment in this rubric demands more cooperation, interaction, flexibility and encompasses both strategic and non-military attributes at a much wide-ranging dimension, by defying the conventional understanding of alliance networks. Within this broad setting, India and the Gulf Cooperation Council (GCC) seek to redefine their partnership with a fresh orientation and nurture a reciprocal relationship through their shared political, historic and cultural linkages. As an emerging economy, India harps on the geo-strategic and geo-economic primacy of the GCC and acknowledges this regional bloc as its promising source of energy and reliable partner in pursuit of its national interest vis-à-vis China and Pakistan. Likewise, the Gulf monarchs are attracted to India’s democratic political tradition and ever-growing significance in world politics and recognize New Delhi’s unequivocal cooperation and support in advancing the politico-economic necessities of the region. This paper examines the efficacy of strategic, energy, maritime and economic security realms, and cultural quotients as crucial determinants behind the success of strategic partnership that these two regional powers seek to solidify in this polycentric world, drawing from the theoretical framework of alliance formation both from the Cold War and post-Cold War perspectives. This article also unravels the presence of divergences that affect their relationship and concludes by highlighting the significance of India-GCC partnership as the representation of South-South cooperation in this critical world scenario.